2021
DOI: 10.3390/ijerph18189862
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Turnover Intention among Male Nurses in Korea

Abstract: The study examined predictors of male nurse turnover intention in Korea using data collected from Korean hospitals. The results were obtained based on a secondary analysis of data previously collected from 306 male nurses in 16 regions of Korea from December 2014 to February 2015. Our findings suggest that male nurse turnover intention is predicted by (1) individual factors: single (B = 0.93, p = 0.008); (2) organizational factors: organizational commitment (B = −0.36, p < 0.001), job satisfaction (B = −0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The possible explanation is that a rational promotion system increases physicians' continuous commitment to the organization, increase the well-being of doctors institutionally and meet the professional needs. And similar results have been reported in Korea and China to explain the phenomenon that Promotion system affects organizational commitment ( 17 , 18 , 36 ). As a result, organizations with a competent promotion structure and adequate human resource staffing within the department may give better growth opportunities and a more compassionate load to physicians, resulting in a positive effect on organizational commitment ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 85%
“…The possible explanation is that a rational promotion system increases physicians' continuous commitment to the organization, increase the well-being of doctors institutionally and meet the professional needs. And similar results have been reported in Korea and China to explain the phenomenon that Promotion system affects organizational commitment ( 17 , 18 , 36 ). As a result, organizations with a competent promotion structure and adequate human resource staffing within the department may give better growth opportunities and a more compassionate load to physicians, resulting in a positive effect on organizational commitment ( 37 , 38 ).…”
Section: Discussionsupporting
confidence: 85%
“…This calls for organization commitment in seeing to the welfare of health workers. This will not only improve quality of work life but also reduce turnover intensions [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the influences of both historical and realistic factors (this issue will be further discussed in the "Discussion" section), across almost all industries (including the education industry) in China-Mainland, having a job paid by government is considered to be steadier and promising (Tan, 2009;Lin, 2019). To date, although there is less direct evidence about the relationship between self-occupation stereotypes and turnover intention, there actually are several studies in other industries suggesting the significant correlation between negative stereotypes and turnover intention (von Hippel et al, 2013;Park et al, 2014;Kim and Moon, 2021). For example, Park et al (2014) found that, in South Korea, those male nurses who possess the stereotypes that females than males are more suitable for nursing displayed a significant turnover intention.…”
Section: Occupation Stereotypesmentioning
confidence: 99%